The other in Ibn Lincoln's poetry, "an analytical reading - Jabr, arkan Raheem (Al-Adab Journal, 2021)
This paper represents the relation of the poet Ibin Link al-Basrai with the other, who describes as a human (poet or linguist, or Grammarian), and describes the other as a time or a nature. The study sheds light on contradictions and agreements which appears in his relation with the other throughout a behavior depends on the poet's feeling, thought, and what is harmonized with his purposes. The research deals with the concept of the other and the biography of the poet , and it is concentrated on the poet's relation with the poets of his age such as Al-Mutanabi, Abe Al-Hethim, and the grammarian Mabrman, and his attitudes about who preceded him as Abi Nawas and Abi Tammam . And it exposes negatively and positively his relation with the time, and his relation with the nature which became a relieve for his worries.